A remark on the Brézis–Browder theorem in finite dimensional spaces. (4th March 2018) - Cotrina, John
Abstract: Brézis and Browder gave an important characterization of maximal monotonicity for linear operators, in reflexive Banach spaces. In this paper, we show that this characterization also preserves the maximal p -monotonicity, in finite dimensional spaces.